Surgical outcomes of patients with duodenal vs pancreatic neuroendocrine tumors following pancreatoduodenectomy. Issue 3 (29th May 2020) - Dong, Ding‐Hui; Zhang, Xu‐Feng; Lopez‐Aguiar, Alexandra G.; Poultsides, George; Rocha, Flavio; Weber, Sharon; Fields, Ryan; Idrees, Kamran; Cho, Clifford; Spolverato, Gaya; Maithel, Shishir K.; Pawlik, Timothy M.
Abstract: Background: To investigate the short‐ and long‐term outcomes of patients undergoing pancreaticoduodenectomy (PD) for duodenal neuroendocrine tumors (dNETs) vs pancreatic neuroendocrine tumors (pNETs). Method: Patients undergoing PD for dNETs or pNETs between 1997 and 2016 were identified from a multi‐institutional database. Overall survival (OS) and recurrence‐free survival (RFS) were evaluated. Results: Among 276 patients who underwent PD, 244 (88.4%) patients had a primary pNET, whereas 32 (11.6%) patients had a dNET. Following PD, postoperative morbidity and mortality were comparable. While the total number of lymph nodes examined was similar between the two groups (median, dNETs 15.0 vs pNETs 13.0; P = .648), patients with dNETs had a higher incidence of lymph node metastasis (LNM) (60.0% vs 38.2%; P = .022) and a larger number of metastatic nodes (median, 3.5 vs 2.0; P = .039). No differences in OS or RFS were noted among patients with dNETs vs pNETs in both unadjusted and adjusted analyses. Among patients who recurred after PD, patients with dNETs were more likely to recur early (within 2 years, 100% vs 49.2%; P = .029) and at an extrahepatic site (intrahepatic‐only recurrence, 20.0% vs 54.1%; P = 0.142) vs patients with pNETs. Conclusions: Patients with dNETs and pNETs had a similar prognosis following PD. Data on differences in the incidence of LNM, as well as in recurrence time and patterns may help to inform the treatment of these patients.